NILAI KEARIFAN LOKAL PADA FILM TARUNG SARUNG - Ramadhani, Nabila Eka Asri (JURNAL KOMUNITAS, 2022)
This study focuses on "Representation of the Meaning of Local Wisdom Values ​​in Tarung Sarong Film". This study aims to determine the representation of the meaning of local wisdom values ​​of the Bugis tribe in the film Tarung Sarong. This film presents forms of local wisdom originating from the Bugis tribe in the city of Makassar. The film “Tarung Sarong” is a drama, religion and action genre film. This film tells the story of a rich businessman's son who always causes problems so his mother sends him to Makassar city to learn how to respect someone and obey God through various forms of local wisdom that exist there. In this study, researchers used descriptive qualitative methods. The data analysis technique used is the semiotic theory of Roland Barthes, with the stages of analysis that include denotation, connotation, and myth. The denotative meaning is the actual meaning that is clearly seen in the film and becomes the initial meaning. Connotative meaning is an additional meaning in the form of words that can strengthen the initial meaning and contain certain feelings or values. Meanwhile, the meaning of myth is a meaning that has ideology, culture, or people's beliefs. The results of this study are that there are several forms of local wisdom that represent the value of self-esteem in the Bugis ethnic community in the film "Tarung Sarong".